Strategi Peningkatan Kesadaran Sertifikasi Halal Pelaku UMKM Kabupaten Sampang dalam Meningkatkan Daya Saing Produk - Faqih faqih; Nasrul Hadi; Rizky Yansah (IQTISODINA, 2025)
Halal certification is an important aspect in ensuring consumer trust and enhancing the competitiveness of MSME products, particularly in Muslim-majority regions such as Sampang Regency. Although the level of awareness among MSME actors regarding the importance of halal certification is relatively high, the number of certified businesses remains low. This study aims to analyze the level of awareness of MSME actors, identify obstacles in the halal certification process, and formulate strategies to improve halal certification awareness. This research employs a qualitative approach using a descriptive case study method through observation, interviews, and documentation. The findings reveal that the main obstacles include complex procedures, limited access to information, certification costs, and insufficient assistance. The study concludes that improving halal certification awareness requires integrated strategies involving socialization, education, technical assistance, and sustainable policy support to enhance MSME product quality and competitiveness.